Designing Overall Equipment Effectiveness (OEE) Measurement Application: Case Study in PG Krebet Baru II - Astuti, Retno; Maknunah, Lu'lu' Ul; Effendi, Mas'ud (Jurnal Teknologi Pertanian, 2014)
PG Krebet Baru II does not have a measuring tool that can help analyze its machineries performance. An effective way to analyze machine performance is OEE measurement based on Availability ratio, Performance ratio, and Quality ratio measurement. This study aims at getting OEE measurement application and giving the OEE result quickly and accurately. OEE measurement application was designed using Microsoft Visual Basic 6.0 as programming language, Microsoft Access 2007 as the database and using the prototype approach. Based on the results, prototype COPRA (Computation of OEE Process Rapidly and Accurately) was created. Prototype COPRA has a main menu consisting of Home, Input Data and Data OEE. It has a menu bar consisted of System (has two sub menus which were data delete and application exit), File (has three sub menus which were machine data, operator data and OEE report) and Help (has three sub menus which were user guide, contact person and about). Verification test results and validation test concluded that prototype COPRA was verified and valid. COPRA application passed testing and was ready to be used based on trial result that showed the difference in the COPRA and manual measurement result was less than 0.15%.Keywords: COPRA application, Designing application, OEE measurement